(untitled) (Indian Journal of Animal Production and Management, 2014)
Two hundred day old chicks were reared on deep litter system up to 6 weeks of age to evaluate the comparative performance of broiler chicken during four different seasons viz. spring, summer, autumn and winter in Kashmir Valley of Jammu and Kashmir. The season had significant (P<0.05) effect on all the parameters under study. Highest body weight (1449.8 g) was observed during summer season and lowest (1038 g) in winter season. Best feed conversion ratio was found during summer followed by spring and autumn seasons. Highest mortality (7.55 per cent) was observed during winter season and lowest in summer (3.68 per cent). The gross profit per bird was significantly highest during summer season and lowest during winter season. The cost of broiler production per kg live weight was found to be least during the summers as compared to other seasons. The results indicate that summer season appears to be ideal season for optimum performance and maximum returns from broiler rearing in Kashmir Valley.